Characterization of 3-D wave flow regimes on falling liquid films. (February 2018) - Guzanov, V.V.; Bobylev, A.V.; Heinz, O.M.; Kharlamov, S.M.; Kvon, A.Z.; Markovich, D.M.
Highlights: Three scenarios of wave evolution detected depending on liquid flow rate. 3D waves decay downstream when flow rate is less than a threshold value. Steady-state 3D wave regimes are observed when flow rate exceeds a threshold value. Characteristics of the steady-state regimes are insensitive to the initial conditions. Abstract: Experimental study of wave evolution on the surface of isothermal liquid films falling down vertical plate conducted by means of field measuring system has revealed three typical scenarios of the evolution in the range of low and moderate liquid flow rates. At low liquid flow rates transverse modulation of 2D waves develops without formation of 3D waves. Two dimensional waves break up into 3D waves only when Reynolds number Re of the film flow exceeds some threshold value which depends on physical properties of working fluid. The fully developed steady-state 3D wave regimes are observed when Re exceeds another threshold value. The obtained results allow to determine the boundaries within which the adequate comparison between modeling and experiments on 3D wave flow of liquid films is possible.